Short story learning model and its role in improving motivation, activity, critical thinking, and learning outcomes of elementary school students - Lestyani, Karen Amalin; Agusta, Akhmad Riandy; Dhania, Hanrezi (Institute of Computer Science (IOCS), 2024)
The problem in this study is the low motivation, activity, critical thinking skills of students in class V SDN Pasar Lama 1 due to one-way learning, not using concrete learning media and attracting students' attention, not applying meaningful learning activities, not applying learning models that focus on developing each indicator of critical thinking skills, there is no combination of learning models that can arouse student motivation. The purpose of this study was to analyze the increase in learning motivation, student activity, critical thinking skills and student learning outcomes. This research applies Classroom Action Research (PTK) because it aims to improve the learning process to increase motivation, activity, critical thinking and learning outcomes through a solution, namely the CERPEN innovative learning model. This research was conducted in 4 meetings by implementing all stages of PTK consisting of planning, implementation, observation and reflection. The subjects of this study were students of class V-B SDN Pasar Lama 1, totaling 26 students consisting of 12 boys and 14 girls, in the second semester of the 2022/2023 school year. The data collected is qualitative data obtained through observations of teacher activities, student motivation, student activities, and critical thinking skills, then using quantitative data obtained by student learning outcomes through techniques obtained by individual and group written tests. Data analysis in this study used descriptive analysis techniques and analysis of the relationship between research aspects described using tables, graphs and interpretations with percentages.